Analisis Penerapan Manajemen Perubahan Budiman Swalayan Padang - Karimah, Nurul Faizatil; Chairinisa, Zihan Nurul; Putri, Yesica Julia; Sari, Celsi Karmila; Putra, Ramdani Bayu (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
This study examines the implementation of change management at Budiman Swalayan, Padang, using a qualitative approach. The primary focus is on business adaptation to local cultural values and digital transformation in customer service. Data were collected through in-depth interviews and participant observation, then analyzed to understand the impact of these changes on loyalty and market competitiveness. Results indicate that management emphasizing Islamic values and digital innovation improves service quality and consumer loyalty.